Short Communication: Dental Trait Variation and Age Determination Based on Dental Wear: A Preliminary Study of Javanese - Myrtati D. Artaria (Dental Anthropology Association, 2007)
This preliminary study describes the dental crown morphology of 14 Javanese of known sex and age. The purpose was to suggest what dental traits to look for when studying a bigger sample from Java. Of 21 traits looked for, traits occurring in the sample were shovel shape, winging, tuberculum dentale, interruption groove, canine distal accessory ridge, premolar accessory ridges, premolar accessory marginal tubercles, premolar multiple lingual cusps, cusp 5, cusp 6, Y5 pattern, cusp 7, protostylid, deflecting wrinkle, anterior fovea, hypocone, and Carabelli's cusp. Dental wear overestimated actual ages because the observed rate of wear was less than in the reference sample.